SISTEM PENDUKUNG KEPUTUSAN PENILAIAN EVALUASI PROSES BELAJAR MENGAJAR (PBM) DOSEN DI POLITEKNIK HASNUR BANJARMASIN MENGGUNAKAN METODE AHP DAN SAW - Ramadhani Noor Pratama; Marhusin , (Program Studi Teknik Informatika, Politeknik Hasnur, 2016)
For view the result of lecturer’s teaching and learning process (TLP) in a college need an evaluation assessment. The result of the lecturer’s teaching and learning process can be view by using one of the method in a decision support system (DSS). Evaluation assessment which not use the method of decision maker system will yield an ineffective result. Therefore, there is need a decision support system that will make the good decision. This decision support application system is a decision support for evaluation assessment of lecturer’s teaching and learning by using AHP-SAW method. AHP-SAW calculation process in this application use the criteria that refers to the lecturer’s teaching and learning process in Hasnur Polytechnic. This decision support system will help to make an evaluation assessment of teaching and learning process of all lecturers, to change the criteria and the ranked value of the criteria, and to change the value. The result of this system is all alternatives ranked of assessment result. In order to this information can be a consideration for the next policy (follow-up evaluation) from the decision maker. So that, these policies will provide a positive impact for the advancement and improvement of lecturer’s teaching and learning process in Hasnur Polytechnic. Key words: Decision Support System (DSS), AHP, SAW, the evaluation of the Lecturer’s teaching and learning Process (TLP). Hasnur Polytechnic Banjarmasin.